Effect of Garcinia mangostana Linn. Pericarp Extract Supplementation on Lipid Profile and Glycemic Parameters in Elderly Patients with Type 2 Diabetes Mellitus: A Double-Blind Randomized Controlled Trial - Yosef Purwoko; Heri Nugroho; Siti Setiati; Banundari Rachmawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Type 2 Diabetes Mellitus (T2DM) in the elderly is frequently accompanied by dyslipidemia, increasing cardiovascular risk. Mangosteen pericarp, derived from Garcinia mangostana Linn., contains xanthones with antioxidant and anti-inflammatory properties that may improve metabolic parameters. The aim of this study is evaluate the effect of mangosteen pericarp extract supplementation on lipid profile, glycemic parameters, and insulin resistance in elderly patients with T2DM. This double-blind randomized controlled trial included 72 elderly T2DM patients allocated into a supplementation group (n=36) and a placebo-controlled group (n=36). Consecutive sampling was used for this study. Baseline and post-intervention assessments included fasting blood glucose, HbA1c, serum insulin, HOMA-IR, total cholesterol, LDL, HDL, and triglycerides. Within-group and between-group analyses were performed using parametric or non-parametric tests as appropriate, with p <0.05 considered statistically significant. Significant differences in baseline HbA1c and LDL levels were observed between groups (p<0.05). After intervention, a significant between-group difference was found only in HDL levels (p<0.05). Delta analysis demonstrated significant improvements in LDL and HDL in the supplementation group compared with controls (p<0.05). No significant differences were observed in fasting glucose, HbA1c, insulin levels, or HOMA-IR. Mangosteen pericarp extract supplementation significantly improved LDL and HDL levels but did not significantly affect glycemic control or insulin resistance.